Lexicons and Cultural Meanings in the Melasti Ritual of Sema Agung Village - Ni Komang Nandia Bramesti; Budasi, I Gede; Wedhanti, Nyoman Karina (EDULIA: English Education, Linguistic and Art Journal, 2026)
This research aims to identify and analyze the lexicon used in the Melasti ritual and its cultural meaning in Sema Agung Village, Klungkung Regency. This study was conducted using a qualitative design with the ethnolinguistic approach. The instruments in this study were the researcher, observation sheet, interview guide, and smartphone. The data were obtained through observation and in-depth interviews with four selected informants. The data was also gathered using four main stages by Miles et al. (2014), including data collection, data condensation, data display, and conclusion drawing. Based on the data analysis, the study result shows forty (40) lexicons related to the procedure of the Melasti ritual found along with the cultural meaning. These findings show that the lexicons reflect the close relationship between language, culture, and religious traditions in preserving Balinese cultural heritage for future generations. It was expected that this study would serve as a reference for other researchers interested in Ethnolinguistics, particularly in the lexicon of the Melasti ritual. Keywords: Cultural Meaning, Ethnolinguistic, Lexicon, Melasti Ritual.